Management and Dental Treatment of Facial Palsy due to Inferior Alveolar Nerve Block in Multiple Sclerosis Patient - Siddiqui, Humayun; Ikram, Kashif; Maqbool, Sana; Khan, Tooba Zafar; Qazi, Aaila Jamil (Journal of Orofacial Research, 2014)
Facial palsy, a common cranial nerve disorders, results in a characteristic facial distortion has an association with multiple sclerosis but precise clinical vignette is lacking. During dental treatment, facial nerve palsy is rare and may be confederate with local anesthesia. We present a case of facial palsy following inferior alveolar block in an attempt to remove lower third molar, occurred 24 hours after the administration of anesthesia showed right side facial weakness, difficulty in eye closure and minimal swelling on the buccal surface of right side and subside within 2 to 4 weeks in a 24-year-old female patient having multiple sclerosis reported to a private clinic are discussed.